Folklore Research and its New Challenges: From the Ethnography to Netografy - Gasouka, Maria; Arvanitidou, Zoi; Xanthippi, Foulidi; Evagelia, Raptou (Mediterranean Journal of Social Sciences, 2012)
Folklorists use the ethnographic method enriching it with anthropological background information. Ethnography is a methodthat describes a culture and its â€œwisdomâ€. Ethnography is interested in the reasons of change of a specific culture and/or the ways ofbreaching and restoring the dominant cultural class and to understand the fragile and fluid processes of social control and the rules laiddown by the members (of the culture) in order to maintain their cultural characteristics. In recent years the Internet became a culturalenvironment without boundaries, which confirms the claim of Dundes and Pagter (1992) that the urban folklore allows the coexistence ofindividuality within the collective identity of each folk group. In online communities multipurpose virtual environments are developed(Economou, 2006) creating virtual locations (places) and developing social interactions and cooperation. In these environments,ethnographic research produces new terms such as netography, cyberethnography, cyber-nations, digital indigenes, digital settlers,digital immigrants, etc. Virtual communities and networks pose particular challenges and opportunities for ethnographic research, as theyrepresent a huge archive of human activity and unprecedented volatility (Jones, 1999, Lindlif and Shatzer, 1998). Virtual, field researchstudies, with increasing interest, a social world which is characterized both as global and digital, which was previously ignored byconventional ethnography (Hine, 2005). This makes the ethnography of digital life an important aspect of contemporary social research,as we will try to demonstrate with this paper.